Implementation of National Agency for Science, Engineering, Infrastructure, and Innovation (NASENII) Programme for Economic Development: A Study of Nigeria - Musa Zakari; Yemi Ogulela; Nwamaka P. Ibeme; Mark Ochala (Governance and Society Review, 2024)
The current study examines the implementation of National Agency for Science, Engineering, Infrastructure, and Innovation (NASENII) Programme for economic transformation in Nigeria. The study adopted systems theory as theoretical frame work and adopted survey and documentary research design. Primary and secondary method of data collection was used to collect data and was analysed through statistical technique. The results revealed that the National Agency for Science, Engineering, Infrastructure, and Innovation (NASENII) has successfully implemented the national policy on science, technology, and innovation. The agency has achieved its goals by fostering a robust innovation ecosystem, strengthening Nigeria's science, technology, and innovation capabilities to support the evolution of a modern economy. These efforts have contributed to job creation, wealth generation, reduced reliance on imports, increased exports, and overall national development. Additionally, NASENII has laid the groundwork for sustainably driven scientific and technological innovations to flourish in the future. Inadequate fund and raw materials for production are the major challenges affecting the productivity of NASENII in Nigeria. The study recommends that Federal Government should vote for more funds in order to purchase raw materials for production in order to stimulate the growth of SMEs, agriculture, and power generation to reduce poverty.